2020
DOI: 10.1038/s41598-020-71223-3
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting to metallic transition with outstanding optoelectronic properties of CsSnCl3 perovskite under pressure

Abstract: inorganic non-toxic metal halide perovskites have taken the dominant place in commercialization of the optoelectronic devices. The first principles simulation has been executed with the help of density functional theory to investigate the structural, optical, electronic and mechanical properties of nontoxic csSncl 3 metal halide under various hydrostatic pressures up to 40 GPa. The analysis of optical functions displays that the absorption edge of CsSnCl 3 perovskite is shifted remarkably toward the low energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 59 publications
7
81
0
Order By: Relevance
“…The calculated bandgaps at a pressure of 0 GPa of the Cs 3 Bi 2 I 9 , Cs 3 Bi 2 Br 9 , and Cs 3 Bi 2 Cl 9 are 2.38, 2.60, and 3.08 eV, respectively. The scissor value approach was used to establish the band structure of the Cs 3 Bi 2 X 9 perovskites in order to obtain the accurate value for the Cs 3 Bi 2 X 9 perovskites when they reached the optimal bandgap of the Shockley-Queisser theory and the transition from semiconductor to metal; this methodology overcame the limitations of the GGA-PBE calculation method and has already been applied in the study of the photoelectric properties of the CsSnCl 3 perovskite at HPs [40]. Many experimental studies have been conducted regarding the bandgaps of the Cs 3 Bi 2 I 9 , Cs 3 Bi 2 Br 9 , and Cs 3 Bi 2 Cl 9 perovskites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated bandgaps at a pressure of 0 GPa of the Cs 3 Bi 2 I 9 , Cs 3 Bi 2 Br 9 , and Cs 3 Bi 2 Cl 9 are 2.38, 2.60, and 3.08 eV, respectively. The scissor value approach was used to establish the band structure of the Cs 3 Bi 2 X 9 perovskites in order to obtain the accurate value for the Cs 3 Bi 2 X 9 perovskites when they reached the optimal bandgap of the Shockley-Queisser theory and the transition from semiconductor to metal; this methodology overcame the limitations of the GGA-PBE calculation method and has already been applied in the study of the photoelectric properties of the CsSnCl 3 perovskite at HPs [40]. Many experimental studies have been conducted regarding the bandgaps of the Cs 3 Bi 2 I 9 , Cs 3 Bi 2 Br 9 , and Cs 3 Bi 2 Cl 9 perovskites.…”
Section: Resultsmentioning
confidence: 99%
“…The spin-orbit coupling is not considered due to the high computational cost. Previous studies have shown that higher levels of calculation (including the spin-orbit coupling, the GW method, or hybrid functionals) obtain more accurate bandgaps; However, they induce little change in the band structure of the heavy-metal halide perovskites [40].…”
Section: Computational Model and Methodsmentioning
confidence: 99%
“…At this time, leadfree halide perovskites were discovered with lower toxicity and higher stability and have attracted great interests [5][6][7][8][9]. There are many choices for the replacement of Pb 2+ by other benign metal ions, including the incorporation of isovalent Sn 2+ ions [10] and substitution of trivalent Bi 3+ or Sb 3+ ions forming the similar composition as Cs 3 Bi 2 Cl 9 [11][12][13]. However, those materials are either limited by stability challenges [14] or with lower electronic mobility because of the lower symmetry nonperovskite structure [15].…”
Section: Introductionmentioning
confidence: 99%
“…35 The rst-principle calculations were successfully implemented to cubic perovskite compounds to analyze different physical properties. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] The substitution of element, 35,36 doping, 10,37,38 or applying hydrostatic pressure [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] can change the physical properties of cubic perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43][44] The band gap of halide cubic perovskites CsBX 3 (B ¼ Sn, Ge; X¼ Cl, Br) was decreased to zero by applying external pressure, resulting in a semiconductor to metallic transition. [45][46][47][48][49] The rst-principle investigations under hydrostatic pressure have also been done for Ca based cubic alkali halide perovskites KCaX 3 (X ¼ F, Cl) 50,51 and ACaF 3 (A ¼ Rb, Cs). 52,53 The band gap of KCaF 3 and RbCaF 3 were shied from indirect to direct by applying hydrostatic pressure of 13.5 and $14 GPa, respectively.…”
Section: Introductionmentioning
confidence: 99%